(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Many employment generation programmes are being introduced by the govt of India to fulfill the gap of employment generation in rural India. Gandhi national rural employment guarantee act is that the first ever act within the history of India to supply guaranteed work and wage. This paper studies the effect of MGNREGA on the generation of employment, sort of work done under this statute and up to what extent this programme is successful in poverty alleviation in rural India. Many researchers have found that this programme features a huge impact on the utilization structure of rural India. this paper studied and descriptions the role of MGNREGA in enhancing the livelihood of poor rural people through twin incorporation of labor with skill. Also, there’s the necessity of overcoming the procedure of payment.